High-Temperature Oxidation of a Zr–1Nb Alloy with a Protective Cr/Ta Coating; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 17, Suppl. 1 - Syrtanov M. S. Maksim Sergeevich; Korneev S. P. Stepan Pavlovich; Abdulmenova A. V. Anastasiya Vladimirovna; Lomygin A. D. Anton Dmitrievich; Mishchenko D. D. Denis Dmitrievich (2023, 2023)
The oxidation and interdiffusion mechanisms of a Zr–1Nb zirconium alloy with a Cr/Ta coating have been investigated. Multilayer Cr(8 μm)/Ta(3 μm) coatings were deposited by magnetron sputtering. The coated zirconium alloy samples were oxidized at 1100°C without isothermal exposure and under exposure for 15–60 min. The coating ceased to act as a diffusion barrier and, consequently, began to delaminate at 60 min of oxidation. Studies on the protective properties of the Cr/Ta coatings were carried out using XRD, SEM, and in situ XRD up to 1250°C. The results showed that during the oxidation process, tantalum diffused into both chromium with the formation of the Cr2Ta phase and zirconium. In situ XRD indicated the formation of the Cr2Zr phase during oxidation for 2 min at 1250°C. The thickness of the residual chromium layer in the case of the Cr/Ta coating was greater than that of the single-layer chromium coating. The possibilities of using Cr/Ta as a coating for fuel cladding were considered.